2016
DOI: 10.1063/1.4966026
|View full text |Cite
|
Sign up to set email alerts
|

Aspect ratio effect on particle transport in turbulent duct flows

Abstract: The dynamics of dilute micron-sized spherical inertial particles in turbulent duct flows is studied by means of direct numerical simulations of the carrier phase turbulence with one-way coupled Lagrangian particles. The geometries are a square and a rectangular duct with width-to-height aspect ratio AR of 3 operating at Re τ,c = 360 (based on the centerplane friction velocity and duct halfheight). The present study is designed to determine the effect of turbulence-driven secondary motion on the particle dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 39 publications
(64 reference statements)
5
17
0
Order By: Relevance
“…At the local level, the DEM simulation should be further refined, considering, e.g., the influence of fluid phase, possibly by using coupled DEM/CFD analyses. It would also be meaningful to compare the DEM-based modeling with the detailed assessment of local phenomena such as secondary flow in the vicinity of wall and complex trajectories of particles, using high-fidelity CFD analysis [74,75]. Finally, the approach from numerical simulation to the accurate and fast prediction of system pumpability should be developed to serve realistic construction projects directly.…”
Section: Discussionmentioning
confidence: 99%
“…At the local level, the DEM simulation should be further refined, considering, e.g., the influence of fluid phase, possibly by using coupled DEM/CFD analyses. It would also be meaningful to compare the DEM-based modeling with the detailed assessment of local phenomena such as secondary flow in the vicinity of wall and complex trajectories of particles, using high-fidelity CFD analysis [74,75]. Finally, the approach from numerical simulation to the accurate and fast prediction of system pumpability should be developed to serve realistic construction projects directly.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, particles tend to deposit at the duct corners. More recently, Noorani et al (2016) studied the effect of varying the duct aspect ratio on the particle transport. These authors considered a higher bulk Reynolds number than Sharma & Phares (2006) and found that in square ducts, particle concentration in the viscous sublayer is maximum at the centerplane.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty and sensitivity analysis, high-fidelity simulations, and particle behaviors will be addressed in future experiments by using multi-data comparisons [51], commercial computational fluid dynamics software [52], and a Malvern particle size analyzer [53] to further analyze the fundamental mechanisms of interactions between flow, water vapor, and evaporation.…”
Section: Discussionmentioning
confidence: 99%